Analisis Kualitas Air Tukad Pakerisan Menggunakan Metode Indeks Pencemaran - I Made Nada; Ni Luh Widyasari; Ni Putu Meilda Florenzia Ekayanti (Program Studi Teknik Lingkungan Unmas Denpasar, 2023)
Tukad Pakerisan is one of the largest rivers in Bali that crosses Gianyar Regency. The increase in population has caused the function of Tukad Pakerisan to decline and become polluted. This study aims to determine the quality and status of quality in the upstream, middle and downstream of Tukad Pakerisan. The results showed that the quality of Tukad Pakerisan in the upstream section had parameters that exceeded the quality standards, namely Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO) and Phosphate. In the middle part, the parameters that exceed the quality standard are Dissolved Oxygen (DO) and Fecal Coliform. On the downstream side, parameters that exceed quality standards are Dissolved Oxygen (DO) and Phosphate. While the results of the calculation of the Pollution Index (IP) at the upstream point are 1.76; midpoint 1.80; and downstream point 1.13 with slightly polluted status.